Role of Emotional Intelligence in Stress Management and Work Performance: Insights from the Malaysian Automotive Industry during the COVID-19 Pandemic - Mas Anom Abdul Rashid; Ruhil Amani Said; Mohd Azman Othman (Current Progress in Arts and Social Studies Research Vol. 10, 2025)
The emergence of the novel coronavirus, SARS-CoV-2, commonly referred to as COVID-19, introduced a new era of challenges for humanity. In the Malaysian automotive sector, the effects of pandemic-induced stress have been keenly felt as organizations confront disruptions to supply chains, production delays, and shifts in consumer demand. In this context, the role of emotional intelligence in mitigating the effects of stress on work performance assumes heightened significance. In response to the World Health Organization’s recent warning on January 18, 2024, regarding the potential resurgence of pandemics, this study investigates the impact of pandemic-induced stress, emotional intelligence, and work performance within the Malaysian automotive industry. While acknowledging certain limitations, the findings emphasize the necessity for organizations to fortify their resilience strategies by prioritizing emotional intelligence development and implementing supportive measures. As organizations brace for future challenges, this study offers actionable guidance for policymakers and industry leaders to enhance employee well-being and organizational resilience in the face of looming uncertainty. In conclusion, this study highlights the critical role of emotional intelligence in moderating the impact of pandemic-induced stress on work performance within the Malaysian automotive industry. Further research within the Malaysian automotive industry and beyond will be instrumental in deepening the understanding of emotional intelligence’s role in shaping resilient and adaptive workplaces.